Cooperative Behavior and Common Pool Resources : Experimental Evidence from Community Forest User Groups in Nepal - Bluffstone, Randy; Dannenberg, Astrid; Martinsson, Peter; Jha, Prakash; Bista, Rjesh (World Bank, Washington, DC, 2015)
This paper examines whether cooperative behavior by respondents measured as contributions in a one-shot public goods game correlates with reported pro-forest collective action behaviors. All the outcomes analyzed are costly in terms of time, land, or money. The study finds significant evidence that more cooperative individuals (or those who believe their group members will cooperate) engage in collective action behaviors that support common forests, once the analysis is adjusted for demographic factors, wealth, and location. Those who contribute more in the public goods experiment are found to be more likely to have planted trees in community forests during the previous month and to have invested in biogas. They also have planted more trees on their own farms and spent more time monitoring community forests. As cooperation appears to be highly conditional on beliefs about others’ cooperation, these results suggest that policies to support cooperation and strengthen local governance could be important for collective action and economic outcomes associated with forest resources. As forest management and quality in developing countries is particularly important for climate change policy, these results suggest that international efforts such as the United Nations Collaborative Programme on Reducing Emissions from Deforestation and Forest Degradation should pay particular attention to supporting governance and cooperation at the local level.